2017
DOI: 10.1007/s13317-017-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the upper reference limit for thyroglobulin antibodies according to the National Academy of Clinical Biochemistry guidelines: comparison of eleven different automated methods

Abstract: Purpose In the last two decades, thyroglobulin autoantibodies (TgAb) measurement has progressively switched from marker of thyroid autoimmunity to test associated with thyroglobulin (Tg) to verify the presence or absence of TgAb interference in the follow-up of patients with differentiated thyroid cancer. Of note, TgAb measurement is cumbersome: despite standardization against the International Reference Preparation MRC 65/93, several studies demonstrated high inter-method variability and wide variation in lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Despite the fact that differences of up to a factor of 100 between different Tg antibody assays have been reported in the literature [ 15 ], 1 particular study showed very good correlation between the assays included in our current study when trying to establish upper reference limits for Tg antibody assays [ 36 ]. According to the latter study, the ULN for the 4 assays tested in our current study should not differ as much as they do, based on the information provided by the manufacturers ( Table 1 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite the fact that differences of up to a factor of 100 between different Tg antibody assays have been reported in the literature [ 15 ], 1 particular study showed very good correlation between the assays included in our current study when trying to establish upper reference limits for Tg antibody assays [ 36 ]. According to the latter study, the ULN for the 4 assays tested in our current study should not differ as much as they do, based on the information provided by the manufacturers ( Table 1 ).…”
Section: Discussionmentioning
confidence: 76%
“…According to the latter study, the ULN for the 4 assays tested in our current study should not differ as much as they do, based on the information provided by the manufacturers ( Table 1 ). For example, the Kryptor assay has an ULN is 33 U/mL; for the LIAISON® assay, it is 100 IU/mL, while the study by D’Aurizio et al could justify similar cutoffs [ 36 ]. If we would apply a cutoff of 100 IU/mL to both assays, this would result in 2,5% discordance instead of 13% discordance.…”
Section: Discussionmentioning
confidence: 99%
“…The similar susceptibility regarding anti‐Tg, especially between Abbott and Roche, is further corroborated by the additional data of the method comparison data, though we did not assess anti‐Tg interference directly and acknowledge the poor agreement of anti‐Tg assays. 15 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of serum levels, despite the lower median of TGAb and TPOAb serum levels in individuals with sufficient vitamin D level compared to those with vitamin D deficiency, no significant differences were observed. Apparently, determining the cut-off measurement of these autoantibodies plays a role in these differences [22]. Tehran thyroid study, in which the median of TPOAb level of individuals with positive titer was considered to be 177 (79-366), was used as a measurement reference in specifying the diagnostic levels in the present research [20].…”
Section: Discussionmentioning
confidence: 99%